A New Approach to Elementary Learning: An Interactive Digital Module for Critical Thinking with Articulate Storyline - Yuli Mulyawati; Elly Sukmanasa; R. Teti Rostikawati; Nurafifah Deas Maharani; Aisyah Nur Azizah (Pedagogia: Jurnal Ilmiah Pendidikan, 2024)
This research aims to develop an interactive digital module based on Articulate Storyline to improve the critical thinking skills of elementary school students. A research and development (R&D) approach with the ADDIE model is used in the development of this module, which includes the stages of needs analysis, interactive module design, development, implementation and evaluation. The research was conducted in fifth grader at one of state elementary school, Bogor City. The results of the expert validation show the feasibility of the material (90%), media (87%) and language (85%), which fall into the category of "very feasible". The effectiveness test through pre-test and post-test showed significant improvements in the aspects of analysis (N-Gain 0.63), Evaluation (N-Gain 0.75), creativity (N-Gain 0.80), and problem solving (N-Gain 0.79). Student responses to the module have been overwhelmingly positive, with an approval rate of 92% for interactivity and 90% for ease of use. This module has been shown to be effective in improving critical thinking skills through interactive features such as simulations, quizzes, and multimedia elements. In conclusion, Articulate Storyline-based modules support 21st century learning by integrating interactive technology to create a satisfying and meaningful learning experience. This research makes an important contribution to the development of innovative learning media to improve students' critical thinking skills at the elementary school level.